Situating the drivers of violence: Building a global movement through national engagement, evidence and action. (3rd August 2018) - Boyden, Jo; Jewkes, Rachel; Ligiero, Daniela; Subrahmanian, Ramya; Taylor, Howard
ABSTRACT: Every year, over 1 billion children experience violence. Violence affecting children undermines their health, education and development, often with negative lifelong consequences and intergenerational impact; in recognition of its impact on sustainable development, combatting such violence is prioritised within the global Sustainable Development Goals (SDGs). The Multi-Country Study on the Drivers of Violence Affecting Children in Peru, Italy, Viet Nam and Zimbabwe sought to understand what drives violence in these countries and what can be done about it, working hand-in-hand with national governments and local research institutes. Preventing violence is complex and strategies to address it in all its forms must be understood and addressed within a child's entire social ecology—including the constantly changing structural and institutional forces that shape childhood. Both the Study's process and its research products are noteworthy. The human-centred design and applied approach, one that yielded national processes of data analysis and understandings of violence, generated a host of outcomes during the life of the study. On a national policy level, these include the engagement of government ministries not typically involved in debates around children's well-being, as well as contributing to legal reforms and budget re-allocations that, in some cases for the first time ever, directed government funding to nationally-led violence prevention research. Using the research as an intervention, the study fostered institutional normative change across all four countries and within the corridors of power that are traditionally slow to respond to violence as a priority issue. The future challenge, currently underway, will be to support national partners as they apply the Study's findings to improve prevention and response programming and advocate for sustainable change.